SELF-EFFICACY: ANALYSIS OF LEARNING OUTCOMES OF TEACHER EDUCATION PROFESSIONALS (PPG) - Darta Darta; Jusep Saputra (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Self-Efficacy (SE) is an essential component in mathematics learning that must be improved so that the teaching performance can convince students. The purpose of this study is how brightspace SPADA (Online Learning System) is developed to measure PPG participants' self-efficacy, which can contribute to the creation of an increase in the quality of education. This study's subjects were PPG participants in the Department of Mathematics Studies in one private LPTK in Bandung, which before the workshop began with online learning. The research method used is the Mixed Method of Embedded Design type and Embedded Experimental Model type. The instrument used was an online test on e-learning and a closed statement SE scale of 10. The analysis used include, (1) Descriptive analysis of online learning outcomes and self-efficacy, (2) Comparative analysis of online learning outcomes between classes (Class A and B) using the Mann Whiney-U test because the data are not normally distributed, (3) Comparative analysis of online learning outcomes between levels, namely junior high, high school, and vocational school (SMP, SMA, and SMK) using ANOVA, (4) Comparative analysis of self-efficacy between classes (Classes A and B) using t-test, because the data is normally distributed, (5) Comparative analysis self-efficacy between levels (SMP, SMA, and SMK) using ANOVA, (6) Analysis of the effect of online learning outcomes on self-efficacy using simple linear regression. The study results are: (1) Descriptive online learning results can be concluded that PPG Mathematics online learning outcomes are above average (≥ 75), based on levels. The result of descriptive statistical data analysis of online learning outcomes is that the average value of participants from SMP, SMA, and SMK is 76.93, 93.12, and 85.92. PPG Mathematics participants' self-efficacy is in the very good category (8.6 from 0-10 intervals), based on the level. Descriptive statistical data analysis obtained the average value of participants from SMP, SMA, and SMK is 8.68, 8.65, and 8.76. (2) There is no significant difference in online learning outcomes between classes A and B. (3) There is no significant difference in online learning outcomes between SMP, SMA, and SMK. (4) There is no significant difference in self-efficacy between classes A and B. (5) There is no significant difference in self-efficacy between SMP, SMA, and SMK. (6) There is no online learning outcomes influence on Self-Efficacy.